2014
DOI: 10.1007/s11908-014-0454-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Diagnosis and Treatment of Interstitial Cystitis/Painful Bladder Syndrome

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a prevalent chronic condition that can be challenging not only to diagnose but also to treat. We review recent diagnostic markers and therapies for IC/BPS from non-medication-based therapies, oral therapies, intravesical therapies, and surgical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 113 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…We also found that bladder/pelvic floor tenderness was associated with deep dyspareunia, independent of painful bladder syndrome, suggesting that myofascial origin or central sensitization may also be important in tenderness of these areas [15]. Myofascial pain could involve tender trigger points in the levator ani or anterior vaginal wall [20,21] due to hyperactive nerve firing within the skeletal muscle reflex arc due to muscle fibre trauma [20] [23]. Sensitization could manifest as hyperalgesia and allodynia [24,25] in normally non-tender structures (e.g., the bladder and pelvic floor); this could occur by amplification of central nervous system nociceptive pathways, or by viscero-visceral convergence or viscero-somatic convergence at the spinal cord that links gynecologic pain to other visceral (e.g.…”
Section: Discussionmentioning
confidence: 65%
“…We also found that bladder/pelvic floor tenderness was associated with deep dyspareunia, independent of painful bladder syndrome, suggesting that myofascial origin or central sensitization may also be important in tenderness of these areas [15]. Myofascial pain could involve tender trigger points in the levator ani or anterior vaginal wall [20,21] due to hyperactive nerve firing within the skeletal muscle reflex arc due to muscle fibre trauma [20] [23]. Sensitization could manifest as hyperalgesia and allodynia [24,25] in normally non-tender structures (e.g., the bladder and pelvic floor); this could occur by amplification of central nervous system nociceptive pathways, or by viscero-visceral convergence or viscero-somatic convergence at the spinal cord that links gynecologic pain to other visceral (e.g.…”
Section: Discussionmentioning
confidence: 65%
“…1 Although there are numerous theories in regard to IC/BPS etiology, its physiopathology still remains unclear and there is a lack of certain treatment. 2 Various diagnostic tests and attempts at treatment lead to a substantial economic burden as well as patient distress. Thus, using biomarkers in diagnosis has garnered greater interest in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Since Hunner's IC characterization was performed, numerous cases of IC with no evidence of bladder wall lesions were confirmed (10). As already said, ICs with mast cells invasion and inflammation, as well as IC due to sensory nerve sensitization show both the presence and the absence of Hunner's ulcers, but their incidence is low.…”
Section: Mast Cells Inflammation and Sensory Nerve Sensitization Drugmentioning
confidence: 84%
“…This suggested the presence of at least two clinical conditions, ulcerative and non-ulcerative IC, depending on the presence or absence of Hunner's ulcers. Ulcerative IC was most common in older people, presenting with increased day and night-time urinary frequency, histological changes and diffuse bladder inflammation; by contrast, non-ulcerative IC was commonly associated with diffuse and often systemic syndromes, such as fibromyalgia (FM), chronic fatigue syndrome (CFS), irritable bowel syndrome (IBS), chronic pelvic pain (CPP), temporomandibular joint disorder (TMD), migraine, vulvodynia, low back pain, sicca syndrome, allergies, asthma, anxiety, and depression and can be alternatively categorized as a functional somatic syndrome (10). The differentiation of the two subtypes was also supported at least in part by the fact that patients with the ulcerative sub-type responded quite well to local therapies while in contrast patients with the non-ulcerative responded less well.…”
Section: Contextmentioning
confidence: 99%